Persuasive Communication by Nibras House Ponorogo (Keniten) Owner to Attract Customers - Erika Novita Aryani; Andhita Risko Faristiana (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
Persuasive communication has become one of the effective means of communication for attracting customer interest due to its strength in delivering good and captivating messages. What sets Nibras House Keniten apart from other stores is its ability to follow fashion trends while prioritizing product quality and comfort. This study aims to analyze the communication strategy applied by the owner of Nibras House Keniten to influence consumer behavior and purchasing interest. The method used is descriptive qualitative with the owner, leader, and administrative staff as sources. The results show that persuasive communication has been effectively utilized to attract customers and enhance the positive image of Nibras House Keniten as a worthy shopping destination. High-quality Muslim clothing, friendly service, and excellent communication on social media and in-person make Nibras House a good shopping choice. They also apply principles such as selective exposure, audience participation, inoculation, and magnitude. With this strategy, Nibras House Keniten optimizes its appeal as a superior and high-quality shopping destination. Additionally, the use of techniques like association, integration, reward, arrangement, and red-herring significantly enhances brand image and customer satisfaction through relevant and engaging product introductions. Thus, persuasive communication proves to be an efficient means of attracting customer interest, supporting the growth of Nibras House Keniten branch in Ponorogo.